Leveraging emerging technologies to enhance public accountability in South African higher education - Smith, L. (South African Journal of Higher Education, 2025)
South African higher education institutions face significant challenges in maintaining transparency, accountability, and efficient governance. Amidst growing demands for improved quality and accessibility, coupled with fiscal constraints, there is a pressing need to enhance public accountability. The article explores the potential of leveraging emerging technologies as a catalyst for addressing these challenges. The article reviews the current landscape of South African higher education and the complexities surrounding accountability mechanisms. It highlights the critical role that technology can play in fostering greater transparency and accountability by facilitating data-driven decision-making, real-time reporting, and stakeholder engagement. Emerging technologies such as blockchain, artificial intelligence, and big data analytics are examined in the context of their potential applications in higher education governance. These technologies play a pivotal role in enhancing accountability by enabling institutions to analyse vast volumes of data, assess academic performance, and identify areas for improvement. Moreover, digital communication platforms and social media offer institutions an avenue to engage with the public, disseminate information, and collect feedback in real-time enabling higher education institutions to showcase their accomplishments, address concerns, and maintain open lines of communication with stakeholders. The article discusses critical considerations, including data privacy, cybersecurity, and digital literacy, to ensure the successful implementation of these technologies. Additionally, it offers a comparative analysis of international best practices in leveraging technology for educational accountability, drawing valuable insights for South Africa's higher education sector. The article concludes by emphasising the transformative potential of emerging technologies in enhancing public accountability in South African higher education. It advocates for a strategic and collaborative approach involving institutions, government bodies, and relevant stakeholders to harness the benefits of these technologies while addressing associated challenges. By embracing technological innovations, South Africa's higher education sector can pave the way for improved governance, increased transparency, and ultimately, better outcomes for institutions and the public they serve.